Survey Study on Fraud Prevention Disclosure Measurement at State Islamic Universities in Indonesia - Wulandari, Sri; Irfan, Andi; Zakaria, Nor Balkish; Mujahidin (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
This study aims to research the extent of information prevention fraud disclosed at PTKIN throughout Indonesia through a theory agency. Types of research This study is quantitative descriptive with descriptive statistical methods and tests of Kruskal Wallis. Amount of the sample in the study This is 34 PTKINs, categorized as